Early cognitive decline after bilateral subthalamic deep brain stimulation in Parkinson's disease patients with GBA mutations. (July 2020) - Mangone, Graziella; Bekadar, Samir; Cormier-Dequaire, Florence; Tahiri, Khadija; Welaratne, Arlette; Czernecki, Virginie; Pineau, Fanny; Karachi, Carine; Castrioto, Anna; Durif, Frank; Tranchant, Christine; Devos, David; et al.
Abstract: Background: Subthalamic nucleus deep brain stimulation (STN-DBS) has demonstrated its efficacy on motor complications in advanced Parkinson's disease (PD) but does not modify disease progression. Genetic forms of PD have been associated with different cognitive progression profiles. Objective: To assess the effect of PD-related genetic mutations on cognitive outcome after STN-DBS. Methods: Patients with STN-DBS were screened for LRRK2, GBA, and PRKN mutations at the Pitié-Salpêtrière Hospital between 1997 and 2009. Patients with known monogenetic forms of PD from six other centers were also included. The Mattis Dementia Rating Scale (MDRS) was used to evaluate cognition at baseline and one-year post-surgery. The standardized Unified PD Rating Scale (UPDRS) evaluation On and Off medication/DBS was also administered. A generalized linear model adjusted for sex, ethnicity, age at onset, and disease duration was used to evaluate the effect of genetic factors on MDRS changes. Results: We analyzed 208 patients (131 males, 77 females, 54.3 ± 8.8 years) including 25 GBA, 18 LRRK2, 22 PRKN, and 143 PD patients without mutations. PRKN patients were younger and had a longer disease duration at baseline. A GBA mutation was the only significant genetic factor associated with MDRS change (β = −2.51, p = 0.009). GBA mutation carriers had a more pronounced post-operative MDRS decline (3.2 ± 5.1) than patients with LRRK2 (0.9 ± 4.8), PRKN (0.5 ± 2.7) or controls (1.4 ± 4.4). The motor response to DBS was similar between groups. Conclusion: GBA mutations are associated with early cognitive decline following STN-DBS. Neuropsychological assessment and discussions on the benefit/risk ratio of DBS are particularly important for this population. Highlights: GBA mutations associates with early cognitive decline after deep brain stimulation. Cognitive decline in GBA mutation carriers was independent of the age. Other PD-related mutations had no effect on cognitive decline post-surgery. Genetic screening may be recommended to advise of future risk of cognitive decline.